Special needs in the early years : partnership and participation - Crutchley, Rebecca (Los Angeles : SAGE, 2018)
Fully up to date with the SEND Code of Practice this book explores all the key contemporary issues relevant to supporting children with special needs in an early years context. Combining theory with practice, it demonstrates how to ensure children's individual needs are at the heart of early years provision. Key topics covered include: • The history and current climate of SEN provision • Working with Parents • Models of special needs provision • Leadership and inclusion • Professional ethics • Multi-agency working • Early intervention • International perspectivesx This core textbook is an essential read for early years students at all levels, and early years practitioners who wish to gain a greater understanding of the core issues affecting special needs provision.
Legislation and policy: towards a particpatory partnership / Rebecca Crutchley -- Working with parents: principles of engagement / Louise Arnold -- Pupil and parent voice: contributions to assessment and planning / Rebecca Crutchley -- Models of SEN provision: the inclusion debate / Ruth Hunt -- Leadership and inclusion: creating and ethos, culture and provision / Athina Tempriou -- Professional ethics: partnership and collaboration in early years / Beate Hellawell -- Early intervention and transition / Rebecca Crutchley and Ruth Hunt -- CPD opportunities for staff working with children with SEND in the early years / Ruth Hunt and Anna Newbold -- Multi-agency working: partnership and collaboration / Estelle Martin.
Includes bibliographical references (pages 169-185) and index.
Keywords: Special education -- Great Britain; Children with disabilities -- Education (Early childhood) -- Great Britain